2017
DOI: 10.1002/adma.201703906
|View full text |Cite
|
Sign up to set email alerts
|

All‐Polymer Solar Cells Based on a Conjugated Polymer Containing Siloxane‐Functionalized Side Chains with Efficiency over 10%

Abstract: A novel wide-bandgap conjugated copolymer based on an imide-functionalized benzotriazole building block containing a siloxane-terminated side-chain is developed. This copolymer is successfully used to fabricate highly efficient all-polymer solar cells (all-PSCs) processed at room temperature with the green-solvent 2-methyl-tetrahydrofuran. When paired with a naphthalene diimide-based polymer electron-acceptor, the all-PSC exhibits a maximum power conversion efficiency (PCE) of 10.1%, which is the highest value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
300
0
4

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(309 citation statements)
references
References 46 publications
5
300
0
4
Order By: Relevance
“…In particular, in 2016, Li et al selected a medium bandgap benzodithiophene‐ alt ‐benzotriazole copolymers with fluorine substitution (J51) as the donor polymer and N2200 as the acceptor polymer to fabricate all‐PSCs and achieved a much higher PCE of 8.27% . Very recently, Huang et al adopted a wide‐bandgap polymer of poly{(4,8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1,2‐b:4,5‐b′]dithiophene‐co‐4,8‐di(thien‐2‐yl)‐2‐(6‐(1,1,1,3,5,5,5‐heptamethyltrisiloxan‐3‐yl)hexyl)‐6‐octyl[1,2,3]triazolo[4,5‐f]isoindole‐5,7(2H,6H)‐dione} (PTzBI‐Si) and achieved the highest PCE of 10.1%, which is also the highest value for all‐PSCs to date, showing the large potential for the NDI‐based photovoltaic polymers …”
Section: Introductionmentioning
confidence: 99%
“…In particular, in 2016, Li et al selected a medium bandgap benzodithiophene‐ alt ‐benzotriazole copolymers with fluorine substitution (J51) as the donor polymer and N2200 as the acceptor polymer to fabricate all‐PSCs and achieved a much higher PCE of 8.27% . Very recently, Huang et al adopted a wide‐bandgap polymer of poly{(4,8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1,2‐b:4,5‐b′]dithiophene‐co‐4,8‐di(thien‐2‐yl)‐2‐(6‐(1,1,1,3,5,5,5‐heptamethyltrisiloxan‐3‐yl)hexyl)‐6‐octyl[1,2,3]triazolo[4,5‐f]isoindole‐5,7(2H,6H)‐dione} (PTzBI‐Si) and achieved the highest PCE of 10.1%, which is also the highest value for all‐PSCs to date, showing the large potential for the NDI‐based photovoltaic polymers …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Thep ower conversion efficiency (PCE) of single-junction fullerene-based PSCs has been attained over 11 %. [8][9][10][11][12][13][14][15][16] Forp ractical applications,t he morphological stability of the all-PSCs against the mechanical and thermal stresses is beneficial for applications in flexible large-scale and stable devices.Although the PCE of all-PSCs has reached 10 %, [15] the performance of all-PSCs still lag behind that of state-of-theart small-molecule-based devices,o wing to the lack of suitable n-type polymer acceptors.T od ate,t he number of polymer acceptors developed for all-PSCs are limited, and only five studies have reported all-PSCs with ap hotovoltaic efficiency over 8% for ab inary system. [5][6][7] Regarding fullerene-based and fused-ring electron acceptor-based devices,a ll-polymer solar cells (all-PSCs) composed of ac onjugated polymer donor and an n-type conjugated polymer offer unique attractions due to their special advantages of morphological stability and flexibility.…”
mentioning
confidence: 99%
“…[4] Recently,P CEs exceeding 13 % have been achieved with proper molecular designs of wideband-gap polymer donors and fused-ring electron acceptors. [8][9][10][11][12][13][14][15][16] Forp ractical applications,t he morphological stability of the all-PSCs against the mechanical and thermal stresses is beneficial for applications in flexible large-scale and stable devices. [8][9][10][11][12][13][14][15][16] Forp ractical applications,t he morphological stability of the all-PSCs against the mechanical and thermal stresses is beneficial for applications in flexible large-scale and stable devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was with the quite recent development with new combinations of polymers, and new electron acceptor transporting polymers, that this field started to move. [243] We have spent some studies on combinations of the TQ1 polymer with N2200 acceptors, [244] similar to the study of Mori et al, [239] but with lower performance. [243] We have spent some studies on combinations of the TQ1 polymer with N2200 acceptors, [244] similar to the study of Mori et al, [239] but with lower performance.…”
Section: Polymer/polymer Blendsmentioning
confidence: 98%